Competency Analysis of Basic Education Teacher Candidates / Analisis Kompetensi Calon Guru Pendidikan Dasar - Sarah Fazilla; Edy Surya (STAI Ma'had Aly Al-Hikam Malang, 2023)
This study aims to analyze the competence of prospective teacher students after the covid 19 pandemic. The method used is review systematic in accordance with Preferred reporting Items for Systematic Reviews and Meta-Analyses (PRISM). Search process focused on article journal about